Mechanisms and regulation underlying membraneless organelle plasticity control. (29th April 2021) - Ismail, Hazrat; Liu, Xu; Yang, Fengrui; Li, Junying; Zahid, Ayesha; Dou, Zhen; Liu, Xing; Yao, Xuebiao
Abstract: Evolution has enabled living cells to adopt their structural and functional complexity by organizing intricate cellular compartments, such as membrane-bound and membraneless organelles (MLOs), for spatiotemporal catalysis of physiochemical reactions essential for cell plasticity control. Emerging evidence and view support the notion that MLOs are built by multivalent interactions of biomolecules via phase separation and transition mechanisms. In healthy cells, dynamic chemical modifications regulate MLO plasticity, and reversible phase separation is essential for cell homeostasis. Emerging evidence revealed that aberrant phase separation results in numerous neurodegenerative disorders, cancer, and other diseases. In this review, we provide molecular underpinnings on (i) mechanistic understanding of phase separation, (ii) unifying structural and mechanistic principles that underlie this phenomenon, (iii) various mechanisms that are used by cells for the regulation of phase separation, and (iv) emerging therapeutic and other applications.